If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -10)(x + -5) = (x + 9)(x + 9) Reorder the terms: (-10 + x)(x + -5) = (x + 9)(x + 9) Reorder the terms: (-10 + x)(-5 + x) = (x + 9)(x + 9) Multiply (-10 + x) * (-5 + x) (-10(-5 + x) + x(-5 + x)) = (x + 9)(x + 9) ((-5 * -10 + x * -10) + x(-5 + x)) = (x + 9)(x + 9) ((50 + -10x) + x(-5 + x)) = (x + 9)(x + 9) (50 + -10x + (-5 * x + x * x)) = (x + 9)(x + 9) (50 + -10x + (-5x + x2)) = (x + 9)(x + 9) Combine like terms: -10x + -5x = -15x (50 + -15x + x2) = (x + 9)(x + 9) Reorder the terms: 50 + -15x + x2 = (9 + x)(x + 9) Reorder the terms: 50 + -15x + x2 = (9 + x)(9 + x) Multiply (9 + x) * (9 + x) 50 + -15x + x2 = (9(9 + x) + x(9 + x)) 50 + -15x + x2 = ((9 * 9 + x * 9) + x(9 + x)) 50 + -15x + x2 = ((81 + 9x) + x(9 + x)) 50 + -15x + x2 = (81 + 9x + (9 * x + x * x)) 50 + -15x + x2 = (81 + 9x + (9x + x2)) Combine like terms: 9x + 9x = 18x 50 + -15x + x2 = (81 + 18x + x2) Add '-1x2' to each side of the equation. 50 + -15x + x2 + -1x2 = 81 + 18x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 50 + -15x + 0 = 81 + 18x + x2 + -1x2 50 + -15x = 81 + 18x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 50 + -15x = 81 + 18x + 0 50 + -15x = 81 + 18x Solving 50 + -15x = 81 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 50 + -15x + -18x = 81 + 18x + -18x Combine like terms: -15x + -18x = -33x 50 + -33x = 81 + 18x + -18x Combine like terms: 18x + -18x = 0 50 + -33x = 81 + 0 50 + -33x = 81 Add '-50' to each side of the equation. 50 + -50 + -33x = 81 + -50 Combine like terms: 50 + -50 = 0 0 + -33x = 81 + -50 -33x = 81 + -50 Combine like terms: 81 + -50 = 31 -33x = 31 Divide each side by '-33'. x = -0.9393939394 Simplifying x = -0.9393939394
| -6+2x=-6x+34 | | 3x-6=-26-7x | | 12x=4x | | 5n+6n=-99 | | -(x+3)-1=4x+7(x+8) | | 4(x+8)=4(3x+12) | | 17+h-3=-9 | | 3x+2-x=-22 | | 5x+25=13x-7 | | 3.2y-5=3+2(1.4x+4) | | 5.3=9.5-0.6x | | 5m^2+4m=-4 | | 3(3y+1)=9y+39 | | 7-5c=c+27 | | 24=5y+3y | | 4(x+3)+2=2(x-3) | | (4x^5+3y)dx-xdy=0 | | -100=4k-8(2+2k) | | 3x+2=1+2x | | 2x-3=37-3x | | .5(x)4=48 | | r-6-26=13 | | sqrt(25)=x | | -2p-3(4-3p)=4(p-3)-12 | | 2x+11y=19 | | x(x)-6=13 | | 4y(3y+3)=118 | | 4x^4+2x^2-6=0 | | 3x-2x^2-4=0 | | -19=11-6X | | (4x-2)4x-2+5x(5x)= | | -5y-7(9y+7)=1+3(-7-y) |